Intelligent sensors - Yamasaki, Hiroo, 1932- (Elsevier, 1996)
Sensors are the front end devices for information acquisition from the natural and/or artificial world. Higher performance of advanced sensing systems is achieved by using various types of machine intelligence. Intelligent sensors are smart devices with signal processing functions shared by distributed machine intelligence. Typical examples of intelligent sensors are the receptors and dedicated signal processing systems of the human sensory systems. The most important job of information processing in the sensory system is to extract necessary information from the receptors signals and transmit the useful information to the brain. This dedicated information processing is carried out in a distributed manner to reduce the work load of the brain. The processing also lightens the load of signal transmission through the neural network, the capacity of which is limited.-Although the performance of the receptors in our human sensory system is not always ideal and is frequently inferior to that of man-made sensors, the total performance is usually far superior to those of our technical sensing systems. The weak points of human receptors are masked by the information processing. This processing makes our sensory system adaptable to the environment and optimizes system performance. The basic idea of this book, which contains new computing paradigms, is that the most advanced intelligent sensing system is the human sensory system. Section I reviews the technologies of intelligent sensors and discusses how they developed. Typical approaches for the realization of intelligent sensors emphasizing the architecture of intelligent sensing systems are also described. In section II, fundamental technologies for the fabrication of intelligent sensors and actuators are presented. Integration and micro-miniaturization techniques are emphasized.-Section III presents advanced technologies approaching human sensory systems, these technologies are not directly aimed at practical applications, but introduce the readers to the development of engineering models of sensory systems. Technologies of integrated intelligent sensors, which will shortly be in use are introduced in section IV. In section V, examples are given of intelligent sensing systems which are used in industrial installations. Hardware for machine intelligence is not integrated at present, but can soon be implemented in the monolithic integrated structure. Without this machine intelligence, new functions, for example, self diagnosis or defects identification, cannot be realized. This section also demonstrates the potential of intelligent sensors in industry. Section VI introduces two interesting topics which are closely related to intelligent sensing systems. The first one is multisensor fusion.-It is expected to be one of the fundamental and powerful technologies for realizing an advanced intelligent sensing systems. The second is visualizing technology of the sensed states for easy comprehension of the dynamic multi-dimensional state. This is useful for intelligent man-machine interfaces. This book will be recognised by readers as a milestone in the rapid progress of intelligent sensors.
Keywords: Intelligent control systems -- Handbooks, manuals, etc.; Detectors -- Handbooks, manuals, etc.; elektronické knihy; electronic books